2005
DOI: 10.1038/sj.ijo.0802882
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a simplified physical activity record by doubly labeled water technique

Abstract: INTRODUCTION:For obtaining reliable information about physical activity in epidemiological studies, validated and easy-touse instruments are required. Therefore, a new simplified physical activity record based on 15-min recording intervals was developed and validated. SUBJECTS: Nonobese volunteers (n ¼ 31). MEASUREMENTS: Physical activity was recorded over a 7-day period without detailed instructions. Energy expenditure was calculated (EE sPAR ) and compared to energy expenditure measured by doubly labelled wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 32 publications
(64 reference statements)
2
47
0
1
Order By: Relevance
“…Moreover, the method does not provide any information about the type, intensity, and duration of each physical activity (Koebnick et al 2005;Plasqui and Westerterp 2007). Hence, accurate alternative methods, validated using the DLW method, are necessary for epidemiological or interventional studies.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the method does not provide any information about the type, intensity, and duration of each physical activity (Koebnick et al 2005;Plasqui and Westerterp 2007). Hence, accurate alternative methods, validated using the DLW method, are necessary for epidemiological or interventional studies.…”
Section: Introductionmentioning
confidence: 99%
“…In laboratory studies, estimates of TEE using the factorial method were within 1% of those obtained from simultaneous indirect calorimetry in a room respirometer (Geissler et al, 1986). In field studies, the method has been shown to produce estimations of TEE for the group that are within 1-5% of those obtained using energy intake-balance as the reference (Acheson et al, 1980; Kalkwarf et al, 1989), and within 3-8% of those obtained using DLW (Conway et al, 2002;Irwin et al, 2001;Koebnick et al, 2005). The DLW validation studies were all done using literature values for the energy cost of different activities, a modification of the method, which tends to increase error (Kalkwarf et al, 1989).…”
Section: Methods and Measurement Issuesmentioning
confidence: 92%
“…Despite the large-scale application, reliability and validity of the measurement of habitual physical activity by questionnaires is low (Shephard 2003). Comparisons with doubly labeled water show generally low correlations with systematic underestimates (Staten et al 2001;Arvidsson et al 2005;Maddison et al 2007;Rush et al 2008), overestimates (Koebnick et al 2005;Mahabir et al 2006), or agreement at the group level with considerable error on an individual level (Bonnefoy et al 2001;Conway et al 2002;Washburn et al 2003). Probably, questionnaires can be adequately used as an activity-ranking instrument.…”
Section: Methodsmentioning
confidence: 99%